Four years of simulated climate change reduces above‐ground productivity and alters functional diversity in a grassland ecosystem. (23rd July 2012) - Cantarel, Amélie A. M.; Bloor, Juliette M. G.; Soussana, Jean‐François
Abstract: Questions: How does above‐ground grassland biomass production respond to change in multiple climate drivers over a 4‐yr period? Can climate‐induced patterns of biomass response be explained by shifts in plant community structure? Does sustained climate change affect the relationships between abundance of functional groups, community‐scale leaf traits and above‐ground production? Location: Perennial grassland in the French Massif Central. Methods: Monoliths extracted from the study grassland were exposed to a simulated climate change corresponding to the air temperature, atmospheric CO2 and summer rainfall conditions projected for 2080. We examined impacts of climate treatments on above‐ground biomass and community structure for 4 yr, and investigated the relationship between biomass production, species diversity and three key functional traits: specific leaf area, leaf dry matter content and leaf N content. Results: Both warming and simultaneous application of warming, summer drought and elevated CO2 were associated with an increase in annual above‐ground biomass at the start of the study, but biomass responses became progressively negative over the course of the experiment. Decreases in vegetation N exports were also observed over time, possibly due to reduced soil N availability under climate change. Taxonomic diversity showed no response to climate treatments, but the relative abundance of grasses decreased under both warming and simultaneous application of warming, summer drought and elevated CO2 after 3 yr. In parallel, legume relative abundance increased in all warmed treatments. Functional diversity responses varied depending on climate treatment and leaf trait. In the control treatment, patterns of variation in annual plant biomass were best explained by functional diversity during the study period. However, in warmed treatments, variation in annual plant biomass was more closely linked to the functional traits of dominant species. Conclusions: Continuous, multi‐year exposure to projected climate conditions has a negative impact on above‐ground biomass in our grassland study system. Our data suggest that climate‐induced decreases in above‐ground biomass may be driven by changes in the relative abundance of plant functional groups, and could also reflect changes in soil nutrient availability. Unlike species diversity, community‐level leaf traits and functional diversity appear to play an important role for above‐ground biomass production, and may have indirect effects on ecosystem stability in changing climates. Abstract : We examined temperate grassland dynamics in response to simultaneous, multiple climate changes. Exposure to projected climatic conditions for 2080 had a progressively‐negative effect on annual aboveground biomass production, driven primarily by ecosystem responses to warming. Climate treatment had no effect on plant species diversity, but variation in plant traits and functional diversity was linked to patterns in aboveground productivity.